Gender and sexuality: An Islamic perspective - Ahmad Shehu Abdulssalam (Universiti Kebangsaan Malaysia, 2006)
This article deals with issues of gender and sexuality from the perspective of religion of Islam, specifically the wasatiyyah approach, which is a moderate trend that takes into account the current situations of Muslims and their relationship with others. By referring to al-Quran and hadith, the relationship between men and women as described in the two sources is analyzed in detail. Issues of interest include husband-wife relationships, marriage and divorce, polygamy, and the etiquettes of socializing and clothing for men and women